The Five-Year Financial Journey of Indian Overseas Bank - Ignatius Joseph; Ms. Emaldarani (International Journal of Engineering and Management Research, 2022)
The banking industry has been a stronghold for India for a long time. It thrives on loans and deposits made by the citizens and companies. But as strong as the industry is, it is hardly invulnerable. It is liable to face the consequences of economic disasters in huge ways. The COVID pandemic is no exception. In the following study we will see its effect on the banking industry before, during and after by taking Indian Overseas Bank as a model. It is found that the bank did well in subscribing loans but has been running at a loss for the past five years.